Financial liberalisation, financial development and economic growth in cameroon: a tri-variate vector error correction modelling approach - Neba Cletus Yah (Journal of Management and Science, 2022)
The aim of this study is to analyse the relationship between financial liberalization, financial development and economic growth in Cameroon. Use is made of a tri- variate VAR model on Cameroon data for the period 1973- 2017. The results obtained show that financial liberalisation and financial development positively affect economic growth. Though financial development does not individually cause economic growth, when considered with financial liberalisation, they jointly cause economic growth.Financial liberalisation and economic growth are individually and jointly found to granger cause financial development. Financial development causes financial liberalisation while economic growth causes financial liberalisation only when jointly considered with financial development. The impulse response functions reveal that economic growth positively responds to both financial development and financial liberalisation though the effect of financial development soon fates out to become negative.Financial development is found to positively react to innovations in financial liberalisation and negatively to economic growth.As concerns financial liberalisation, it negatively responds to financial development and positively to economic growth. Also,variance decomposition reveals that variations in economic growth are mostly explained by its past values, followed by financial liberalisation and finally financial development. Financial development on its part is also mostly explained by its past values followed by financial liberalisation and finally economic growth. Based on all these, the policy recommendation we make is that the on-going financial liberalisation process in the country should be enhanced in view of permitting the financial sector to efficiently play its role in the growth process of the country.